Optimizing Customer Loyalty Strategy Through Service Quality and Word of Mouth Promotion (Case Study on Sri Dewi Kencana Garment in Tangerang Regency) - Calista, Anastasia; Muhyi, Herwan Abdul; Nirmalasari, Healthy (Journal Research of Social Science, Economics, and Management, 2026)
In the highly competitive SME landscape, maintaining customer loyalty is crucial for sustaining business growth and financial stability. This study investigates the influence of service quality and word-of-mouth (WOM) marketing on customer loyalty at Sri Dewi Kencana Garment in Tangerang Regency, Indonesia. The company experienced a 38.8% decline in repeat orders from 2023 to 2024, highlighting critical issues in service delivery and marketing strategies. The research aims to analyse the direct effect of service quality on customer loyalty, examine the impact of service quality on WOM marketing, evaluate the influence of WOM on loyalty, and explore the indirect effect of service quality on loyalty mediated by WOM. A sequential explanatory mixed-methods design was employed. Quantitative data were collected via structured questionnaires from 30 repeat customers and analysed using path analysis, whilst qualitative data from open-ended questionnaires and in-depth interviews provided contextual insights. Results show that service quality significantly affects customer loyalty both directly (? = 0.529; p = 0.002) and indirectly through WOM marketing (indirect effect = 0.404). Service quality also strongly influences WOM (? = 0.917; p = 0.000), and WOM positively impacts loyalty (? = 0.441; p = 0.007). Strategic analysis using SWOT and QSPM identified key priorities: professional image enhancement, standardised service SOPs, and structured WOM deployment. The study concludes that improving service quality and effectively leveraging WOM are critical for sustaining customer loyalty, offering actionable guidance for SMEs in similar contexts.